Bringing the Holy Sepulchre to the west: S. Stefano, Bologna, from the fifth to the twentieth century - Morris, Colin (Studies in church history, 1997)
By virtue of its basic pattern of belief, the Church is committed to looking back as well as forward. In his introductory letter for the Conference which has produced this volume, Andrew Martindale reminded us that ‘doctrine, dogma, and revelation are all pinned to time and place’. Most of all are they rooted in Golgotha and the Holy Sepulchre, the site of the death and Resurrection of the Lord. It is true that, in particular since the Reformation, the theology of the Passion and Resurrection have often been discussed without reference to their historical location. Other Christians in other times, confident that the Holy Sepulchre discovered under Constantine was indeed the authentic place of Christ’s Resurrection, desired to reach out to and to grasp its historical and geographical reality, for these embody the very time and place of their redemption.